A retrospective review of the prevalence and management of anaemia in children in at Red Cross War Memorial Children's Hospital - Wege, Martha Helena (University of Cape Town, 2016)
Includes bibliographical references === Introduction Childhood anaemia is a major public health problem, iron deficiency being most common. WHO estimates anaemia to occur in 24.1% of pre-school South African children. Our study describes prevalence and management of anaemia in children aged 6 - 36 months presenting to a children's hospital. Methods In a retrospective cross-sectional study, laboratory data were used to estimate prevalence of anaemia in children aged 6 - 36 month presenting to medical emergency or ambulatory services of Red Cross Children's Hospital in 2012. A random sample of 50% of anaemic children was sampled for detailed review. Results 2661 subjects were included. Anaemia (H b < 10.5) was found in 40.8 % (1088/2661. Children presenting to medical emergency had a higher prevalence of anaemia compared to those presenting to ambulatory services ( 42.7% vs. 34.9 % ; p=0.001 ). Anaemia prevalence increased with decreasing age with RR 1.25 (95% CI 1.10 - 1.43) and RR 1.15 (95% CI 1.02 - 1.31) in children aged 6 - 11 months and 12 - 23 months respectively compared to children aged 24 - 36 months. Microcytosis was found in 51.3% (558/1088) of anaemic children and in 19.3% (n=303/1573) of children without anaemia ; p<0.001 Folders were reviewed i n 502 children with anaemia , 36.1% had mild anaemia (Hb 10 - 10.5g/dl), while moderate ( Hb 8 - 10 g/dl ) and severe ( Hb < 8 g/dl ) anaemia was found in 52.5% and 11.4% respectively. Breastfeeding for longer than six months was associated with higher risk of microcytic anaemia [RR 1.26 (95%CI 1.08 - 1.47)]. Only 12.2 % (31 /254) of children with microcytic anaemia received adequate iron therapy, 50.0 % (127/254) received no iron therapy. Conclusions Prevalence of anaemia in children presenting to hospital is higher than predicted for well children in South Africa. The risk is higher in younger and acutely sick children. Prolonged breasting is associated with increased risk of microcytosis. Most children with suspected iron deficiency anaemia did not receive appropriate treatment.